2015
DOI: 10.7317/pk.2015.39.6.947
|View full text |Cite
|
Sign up to set email alerts
|

Electron Beam Irradiation to Styela Clava Derived Cellulose Membrane

Abstract: 초록: 셀룰로오스는 탄소와 수소 성분으로 이루어진 탄수화물 복합체로서 β-글루코오스 성분으로 이루어진 식물 세 포벽의 주된 구성성분이다. 미더덕의 피부 각질에서 개발한 동물성 셀룰로오스 유도막에 1-2 MeV 에너지의 전자빔 을 조사하여 C-C 결합보다 C-O 결합이 보다 증가함을 확인하였고, 여러 관련된 결과를 바탕으로 전자빔 조사에 의 해 미세소관을 구성하는 셀룰로오스 미세원섬유들의 탈중합 과정을 일으킬 수 있었다. 셀룰로오스 합성복합체가 이 동함으로써 셀룰로오스 섬유소들을 균일하고 미세하게 변형시킴으로써 골유도재생술을 위한 얇은 μm 단위의 의료 용 유도막으로 활용이 가능할 것으로 사료된다.Abstract: Cellulose is the carbohydrate polymer composed of carbon, hydrogen and β-glucose, and the main composition of plant cell walls. The aim of this study is to evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…During our recent investigations of the effects of EBI on maxillofacial reconstructive polymer materials, we have tried to identify gross and elemental changes in E-beam irradiated CMs [ 9 – 11 ]. E-beam treatment involves accelerating a beam of electrons to near the speed of light and by utilizing an oscillating magnetic field, sweeping the electrons back and forth across the polymers.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…During our recent investigations of the effects of EBI on maxillofacial reconstructive polymer materials, we have tried to identify gross and elemental changes in E-beam irradiated CMs [ 9 – 11 ]. E-beam treatment involves accelerating a beam of electrons to near the speed of light and by utilizing an oscillating magnetic field, sweeping the electrons back and forth across the polymers.…”
Section: Introductionmentioning
confidence: 99%
“…We previously demonstrated that CM can be successfully used as a GBR membrane in combination with particulate bone grafting and that the peculiar characteristics of E-beam irradiated CM are also useful for space maintenance and biocompatibility [ 2 , 5 , 10 , 11 ]. Five surgical factors are required to achieve predictable results with GBR procedures: 1) use of an appropriate membrane, 2) achievement of primary soft tissue healing, 3) creation and maintenance of a membrane-protected space, 4) close adaptation and stabilization of the membrane to the surrounding bone, and 5) a sufficiently long healing period.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations